2015
DOI: 10.1364/oe.23.019854
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in PDMS surface morphology in femtosecond laser treatment

Abstract: We have investigated the effect of the dynamics of crater size on the poly(dimethylsiloxane) (PDMS) surface morphology in fs-laser micro-processing. PDMS surface was processed with varying both inter-pulse interval and inter-spot distance between successive laser pulses. With keeping the interval of 5 ms crater shape is round even if the spot is overlapped in space. But decreasing the interval to 0.02 ms the shape of the crater is no longer round. Decreasing the inter-distance between the craters results in ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…They reported a pulse overlap rate range of 1–2 pulses per micrometer and 1–1.5 μJ to achieve quality separation and fabrication without any visible thermal damages. Moon et al studied the effect of crater size on the surface morphology of PDMS . They studied the PDMS surface with varying both the inter‐pulse interval and the inter‐spot distance between successive pulses.…”
Section: Polymer Materialsmentioning
confidence: 99%
“…They reported a pulse overlap rate range of 1–2 pulses per micrometer and 1–1.5 μJ to achieve quality separation and fabrication without any visible thermal damages. Moon et al studied the effect of crater size on the surface morphology of PDMS . They studied the PDMS surface with varying both the inter‐pulse interval and the inter‐spot distance between successive pulses.…”
Section: Polymer Materialsmentioning
confidence: 99%
“…Ultrafast laser μprocessing was applied to pattern a grid inside PDMS because the damage due to the micro-processing could be minimized. 30,31) We have further confirmed that there are no observable changes in material properties of PDMS due to ultrafast laser engraving by measuring the Poisson's ratio of the grid, which is patterned with varying the laser energy as well as the number of grid patterns on the specimen.…”
Section: Introductionmentioning
confidence: 55%
“…The another possible explanation is a dynamical changes in the portion of vascular endothelium close to the laser irradiated position caused by the mechanical forces accompanied by the shockwaves. We have recently reported that the effect of the dynamics of crater size on the elastomer of poly(dimethylsiloxane) (PDMS) morphology in fs-laser micro-processing [24]. The crater formed on vascular endothelium should deform out of focal position for the confocal microscopic measurement after laser irradiation and be eventually restored to the steady state.…”
Section: Resultsmentioning
confidence: 99%